Maya Angelou : greeting the morning - King, Sarah E., 1957- (Brookfield, Conn. : Millbrook Press, 1994)
Examines the life of the African-Amerian poet, from her childhood in the segregated South to her rise to prominence as a writer.
Includes bibliographical references (p. 45) and index.
Keywords: Angelou, Maya -- Juvenile literature; Angelou, Maya; African American women authors -- 20th century -- Biography -- Juvenile literature; Authors, American; Afro-Americans -- Biography; Women -- Biography